The use of poppy in the food industry in the context of counterdrug activities - Dmitry K. Chirkov (International Journal of Advanced Science and Technology, 2020)
the paper discusses the current state of control on turnover of food cultivation in the context of combating drug trafficking in the Russian Federation. The object of study is illicit poppy (malagarasi plants) as socially negative phenomenon, as well as the activities of the state and society to ensure the effective counteraction to their illicit trafficking. Objective: to examine the relevance of the problem and characteristics of crimes in the sphere of illicit trafficking in poppy (malagarasi plants). Using the method of analytical generalization, it allowed us to establish logical connections on certain problematic issues of counteracting the illicit trafficking in maca-containing products (technical poppy) and bringing individuals to criminal liability for their circulation. In particular, a causal relationship of this pattern was established, namely, criminalizing the illegal trafficking in maca-containing products, since under the cover of supplies from the Czech Republic food poppies produced by Czech companies Unifood, Novolina, Centrum Poppy, Agriwell, Trias, SAIK , Gerste, exported to the Russian Federation about 2000 tons of industrial poppy. An analysis of the information received from the Czech Republic gives reason to conclude that under the “brand” of food poppy produced in the Czech Republic, technical (mixed) poppy is imported into the Russian Federation. The reasons for the appearance of technical poppy on the Russian market can be summarized and formulated as follows: low price of technical poppy, because poppy is not intended for use in cooking and is a waste from the pharmaceutical industry; legal cover for import, distribution, delivery and production of drugs; insufficient control of law enforcement and other competent authorities. In this regard, the author of the article considers it necessary to propose an alternative measure for effective and comprehensive control of the import of food poppy into the territory of the Russian Federation by creating a “Single supplier-importer of food poppy products to the Russian Federation”.